Refinement of the physical and chemical methods for the determination of sugars - Deriy, Elena; Litvynchuk (Vorontsova), Svitlana; Meletyev, Anatoly; Nosenko, Volodymyr (My University, 2013)
The purpose of the work is the comparison of the main existing methods for the determination of sugars to identify the most accurate and easy-to-use in the brewing industry. Experimentally there are optimal methods for determination of sugars for the use in laboratory and industrial conditions of the brewing industry. The correlated coefficients were determined between the results obtained by different methods for the adequate reflection of the main components of sugar share of wort and beer. The essential practical conclusion of the research is the methods for determination of sugars have a sufficiently high accuracy in the determination of the maltose concentration in wort. These methods are the most suitable for the control of kinetics and regulation of production processes.
Keywords: sugars; fermentable sugars; determination; express-analysis; зброджувані цукри; методи визначення цукрів; експрес-аналіз; сбраживаемые сахара; методы определения сахаров; экспресс-анализ; кафедра біотехнології продуктів бродіння і виноробства; кафедра фізики та професійної безпеки